Flu on the Front: the Effects of the Influenza Pandemic of 1918-1919 on the 15th Reserve and 46th Infantry Battalions, Canadian Expeditionary Force - Davis, Renee (Université d'Ottawa / University of Ottawa, 2020)
This study is an examination of the effects of the first two waves of the Influenza Pandemic of 1918-1919 on the Canadian Expeditionary Force in Europe during the final months of the First World War. Using a case-study approach, the study analyzes the experiences of the 15th Canadian Reserve Battalion (Saskatchewan) in England and the 46th Canadian Infantry Battalion (South Saskatchewan) in France from April to 11 November 1918. While the comparison of these two battalions’ experiences is useful to see the how the Canadian Army Medical Corps reacted and responded to the outbreak of pandemic influenza in both locations, it also highlights the impact that the pandemic had on the reinforcement stream in 1918, and demonstrates the greater cost of conscription during the final months of the war. This thesis argues that that the Influenza Pandemic of 1918-1919 affected the Canadian Expeditionary Force’s Hundred Days Campaign in a way that, until now, has not been recognized. Additionally, it argues that the 15th Reserve Battalion was not to blame for bringing pandemic influenza to Bramshott Camp in the fall of 1918, and that the Canadian Army Medical Corps reacted to the outbreak as effectively as possible. Finally, it highlights the experiences of men from Saskatchewan and recounts the stories of soldiers who died of pandemic influenza.
Keywords: Influenza; Pandemic; Canadian; Expeditionary; Flu; Military; Medical; Corps; 1918; CAMC; CEF; Soldiers; War; Reinforcements; Conscripts; COVID-19